2022
DOI: 10.1007/s11356-022-18819-6
|View full text |Cite
|
Sign up to set email alerts
|

Striving towards sustainable development: how environmental degradation and energy efficiency interact with health expenditures in SAARC countries

Abstract: The previous studies focused on environmental issues, identifying their root causes, urging prompt action to reduce environmental degradation. In this context, the current article extends the literature by incorporating the ecological impacts on the health sector and the role of sustainable development. The present study adds to the body of knowledge by examining the relationship between CO 2 emissions, sustainable development, energy efficiency, energy intensity, and health expenditures for SAARC countries fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 67 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…A further study indicated that the corporate social responsibility report published by different corporations, as observed during the pandemic of COVID-19, has a favorable link with investment in renewable energy projects. In agreement with previous research by Zhong et al (2022) , these findings support the hypothesis being advanced. Corporate social responsibility (CSR) reports emphasize the importance of environmental sustainability, so companies invest in renewable energy projects to reduce emissions of hazardous gasses and chemicals by recycling energy resources.…”
Section: Resultssupporting
confidence: 93%
“…A further study indicated that the corporate social responsibility report published by different corporations, as observed during the pandemic of COVID-19, has a favorable link with investment in renewable energy projects. In agreement with previous research by Zhong et al (2022) , these findings support the hypothesis being advanced. Corporate social responsibility (CSR) reports emphasize the importance of environmental sustainability, so companies invest in renewable energy projects to reduce emissions of hazardous gasses and chemicals by recycling energy resources.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, the level of carbon emissions creates health hazards that may impact public health and may have an effect on it; this may lead to increased healthcare costs. With this in mind, Zhang et al ( 98 ) performed an analysis to determine the carbon footprint of the health industry in Australia. They discovered that the use of renewable energy in the health industry in Australia resulted in a decrease of ~14% of the industry's overall carbon footprint.…”
Section: Resultsmentioning
confidence: 99%
“…Health shocks tend to be better handled by households with access to microcredit than households without access to micro-credit. Zhong et al ( 6 ) investigated the long-run linkages between economic and financial risk in the MINT economies from 1984 to 2014. They employed the Wavelet analysis and found the one-way causal association from economic risk to financial risk for Mexico and financial risk to economic risk for Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It argues that large-scale sustainability transitions in transportation, energy, and agri-food socio-technical systems are required to address them (3). The multi-level perspective in this research stream hypothesizes sustainability alterations as green niche innovations battling against existing (unsound) systems and possibly substituting or reconfiguring these systems [e.g., (4)(5)(6)]. Health problems are on the rise as a result of an unsustainable environment (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation